Formulation And Evaluation Of Bilayer Tablet for Bimodal Release of Venlafaxine Hydrochloride - Munira eMomin; Snehal eDumbre; Snehal eDumbre; Pooja eAbhang (Frontiers Media S.A., 2015)
The aim of the present research was to develop a bilayer tablet of venlafexine hydrochloride for bimodal drug release. In the present investigation authors have tried to explore Fenugreek Mucilage (FNM) for bioadhesive sustained release layer. The attempt has been made to combine FNM with well studied bioahesive polymers like Hydroxy Propyl Methyl Cellulose, Carbopol and Xanthan Gum. The formulations were evaluated for swelling Index, ex-vivo bioadhesion, water uptake studies, in-vitro drug release and dissolution kinetics was studied. Substantial bioadhesion force (2.4±0.023 gms) and tablet adhesion retention time (24±2 hrs) was observed with FNM and HPMC combination at 80:20 ratio. The dissolution kinetics followed the Higuchi model (R2 =0.9913) via a non-Fickian diffusion controlled release mechanism after the initial burst. The 32 full factorial design was employed in the present study. The type of polymers used in combination with FNM (X1) and percent polymer replaced with FNM (X2) were taken as independent formulations variables. The selected responses, bioadhesion force (0.11-0.25±0.023gm), amount of drug released in 10 h, Y10 (78.20-95.78±1.24 %) and bioadhesive strength, (19-24±2hrs) presented good correlation with the selected independent variables. Statistical analysis (ANOVA) of the optimized bilayer formulations showed no significant difference in the cumulative amount of drug release after 15 min, but significant difference (p < 0.05) in the amount of drug released after 1 hr till 12 h from optimized formulations was observed. The natural mucilage like FNM could be successfully incorporated into tablet with only 20% replacement with HPMC and it showed good bioadhesiveness and sustained drug release.